Pengaruh Green Product dan Green Marketing Terhadap Keputusan Pembelian Produk Kecantikan Cushion Skintifik di Kota Bima - Apriani, Tita; Ernawati, Sri; Muhajirin, Muhajirin (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This research was conducted in Bima City. The purpose of this study was to determine and analyze the influence of Green Product and Green Marketing on purchasing decisions for Cushion Skintifik beauty products in Bima City. The population in this study were all users of Cushion Skintifik beauty products in Bima City. While the sample in this study amounted to 70 respondents. The sampling technique used was purposive sampling. Data collection techniques were by distributing questionnaires, observation and interviews, and documentation studies. Data analysis used multiple linear regression analysis. The conclusion in the study that Green Product does not have a significant effect on Purchasing Decisions for Cushion Skintifik Beauty Products in Bima City. Green Marketing has a significant effect on Purchasing Decisions for Cushion Skintifik Beauty Products in Bima City. Green Product and Green Marketing have a significant effect on Purchasing Decisions for Cushion Skintifik Beauty Products in Bima City. Adjusted R Square is: 0.307, thus indicating the suitability of the model and the large contribution of Green Products and Green Marketing to Purchasing Decisions of 0.307 or 30.7% and the remaining 69.3% contribution to the Purchasing Decision variable is through other variables not examined in this study.